Immigration émigrative dans Autobiographie de mon père de Pierre Pachet - Misako Nemoto (Itinéraires)
This article examines the dynamics of immigration through Pierre Pachet’s Autobiographie de mon père, a book that explores the life of an individual living through the turmoil of the twentieth century. This seminal work can be read as an attempt to understand what constitutes an individual inextricably entangled in a collective history. In tracing and living again what his father went through, Pachet reveals the subtlety of handing down, of filiation and history, the uncertainties and contingency that surround this transmission from father to son, and tries to rethink our relation to the world, from this new perspective based on the frailty of an individual.